Genetic and Environmental Influences on Delinquency: DF Analysis of NLSY Kinship Data - Rodgers, Joseph Lee (Journal of quantitative criminology, 2001)
This paper follows earlier research (Rowe et al., 1992) in evaluating the basis of family influences on adolescent delinquent behavior. Delinquency is measured in a number of different ways to account for important theoretical distinctions that exist in the delinquency literature. We use recently identified kinship structure in a large national data set—the National Longitudinal Survey of Youth—to estimate genetic and shared environmental influences on self-reported delinquency scores. Our analytic model is based on DF analysis, a regression procedure used to estimate parameters reflecting genetic and environmental influence. Results suggest a consistent and moderate genetic basis to sibling similarity in delinquency and little evidence of a shared environmental basis. A large amount of variance is attributable to nonshared influences and/or measurement error. Our findings suggest that the search for environmental influences on adolescent delinquency should focus on those that are not shared by siblings.